Public awareness of and action towards heart attack symptoms: an exploratory study - Ahmed, Abdullah Abdulmajid Abdo; Al-Shami, Abdulkareem Mohammed; Jamshed, Shazia Qasim; Fata Nahas, Abdul Rahman; Mohamad Ibrahim, Mohamad Izham (MDPI AG, 2020)
Background: Cardiovascular disease (CVD) is still the leading cause of mortality worldwide, and Malaysia is not an exception in this regard. The current research is an attempt to explore symptom awareness of and necessary actions in response to heart attack (HA) among lay public. Methods: This is a cross-sectional study design, and a survey was conducted from May to July 2018 among general public in Kuantan, Pahang state, Malaysia. Results: A total of 393 respondents recruited. Slightly more than one-fourth of the respondents (26.35%) were aware of HA symptoms like pain and/or discomfort in the jaw, neck, or back, while 71.65% showed awareness only of chest pain or discomfort as symptoms. Only 35.6% reported to call an ambulance if they experience someone suering from HA symptoms, while 82% recognized 1 symptom, and only 11.5% recognized all five HA symptoms. Very few respondents, i.e., 1.3% reported awareness about correct recognition of all five HA symptoms. Respondents who had diabetes and hypercholesteremia were more likely to recognize all five HA symptoms. For those who had excellent awareness of all five HA symptoms, the odds ratio (OR) were significantly higher among single respondents (OR 0.023; 95% CI 0.001–0.594), Malay (OR 0.376; 95% CI 0.193–0.733), and those who received information associated with HA (OR 7.540; 95% CI 2.037–27.914). However, those who were aware that HA requires quick treatment had significantly low odds ratio (OR 0.176; 95% CI 0.044–0.710). Conclusions: The awareness of and action towards the signs and symptoms of HA among the public were poor.